ECONOMICS OF THE PHARMACEUTICAL AND MEDICAL DEVICE INDUSTRY supply chain, trade and innovation. - Bhardwaj, Ramesh (Professor of economics) ([S.l.] : ROUTLEDGE, 2024)
This book provides a comprehensive examination of the pharmaceutical and medical device industry, including analysis of its current trade and innovation strategies. Opening with a survey of the global pharmaceutical and medical device industry, Bhardwaj outlines the growing trade and trade interdependence among countries in the global supply chain. He adopts a trade competitiveness approach to analyze patterns of product specialization and examines the drug discovery process and its challenges in translating bioscientific knowledge into lifesaving products. Bhardwaj argues that further economic integration, collaborative R&D, and digital technologies may help accelerate productivity and address global challenges of escalating drug costs, neglected tropical diseases (NTDs), and pandemic risks. The book also considers how the industry may further green its supply chain, and thus contribute to SDG Goals 3 (Good Health and Wellbeing) and 12 (Responsible Consumption and Production), before closing on a review of China and India, major players who have the potential to become drivers of low-cost medical products and innovations. With its evidence-based analysis, this book will be of great interest to researchers in pharmaceutical studies, supply chain management, global health, and health economics, as well as policymakers and professionals interested in the global issues facing the industry.
Keywords: Pharmaceutical technology -- Economic aspects